Prevalence of Kudoa thyrsites (Myxozoa) in South African sardine Sardinops sagax, kingklip Genypterus capensis, and Cape hakes Merluccius capensis and M. paradoxus. Issue 3 (7th October 2019) - Henning, SS; Krügel, M; Manley, M
Abstract : Prevalence of infection with the myxozoan parasite Kudoa thyrsites is not well documented in sardine Sardinops sagax, the Cape hakes Merluccius capensis and M. paradoxus, and kingklip Genypterus capensis . Quantitative polymerase chain reaction assays were used to determine the prevalence of K. thyrsites in wild-caught S. sagax ( n  = 296), Merluccius spp. ( n  = 162) and G. capensis ( n  = 70), harvested in 2015. Sardinops sagax were harvested from the east, south and west coasts of South Africa, whereas M. capensis, M. paradoxus and G. capensis were taken from the west coast only. Relationships between K. thyrsites infection prevalence and fish capture locality, season, sex and size were determined with Chi-square tests. Prevalence was highest in S. sagax (91%), followed by M. capensis and M. paradoxus (87%) and G. capensis (40%). Prevalence was independent of sex of the host for all fish species. In the case of S. sagax only, the prevalence of infection was independent of locality of capture but depended on season, with prevalence lowest during spring and highest during autumn. No significant relationship ( p  > 0.05) was found between infection prevalence and host size for any of the fish species.